Analysis of the Decline of Community Political Participation in the Dumai City Regional Head Election in 2020 - Ahmad Eddison; Alex Dean Serman P; Indra Primahardani (Science and Environmental Journal for Postgraduate, 2022)
This research is motivated by the decline in public political participation in the Dumai city regional head election in 2020. This can be seen based in 2015 the percentage of public political participation was 67.86% while in 2020 63.01% took part in the regional head election. Dumai city. The low level of public political participation is influenced by social and economic factors, situational factors, political awareness factors, trust in the government, and mass media factors. The formulation of the problem in this research is what is the main cause of the decline in the level of public political participation in the 2020 Dumai City Election. Analysis of Descriptive Quantitative Data. The research instrument used a questionnaire consisting of 22 questions. The population in this study was 207,736 residents of Dumaicity with a sample of 100 respondents obtained using the Yemen formula. . of trust in government. Recommendations in this study are for the Dumai City Government to be able to carry out government programs and provide assistance to the community to increase public trust in the government, and for the KPU to be able to hold election socialization both directly and through the masses. media, and so that the public can participate in all forms. political activities and elections in their respective regions, and for further researchers, it is hoped that it can be an inspiration and an illustration for further research.